Effect of Cu doping on properties of RHQT processed powder in tube Nb3Al wires. (April 2021) - Yu, Xuan; Li, Guowei; Hu, Yuanbin; Chen, Ming; Yu, Zhou; Liu, Lian; Chen, Yongliang; Zhang, Yong; Zhao, Yong
Abstract: Powder-in-tube (PIT) Nb3 (Al1- x Cu x )( x = 0–0.04) superconducting wires were fabricated by rapid heating, quenching and transformation (RHQT) process. With the addition of Cu, disordered Nb3 Al A15 phase with stoichiometric composition was formed in the quenched wires and atomic long range ordering occurred during the low temperature annealing process, resulting in improvement of T c, J c and B irr performance compared to the pure Nb3 Al sample. The highest T c of 18.0 K, narrowest ΔT c of 0.6 K and best layer J c of about 30481 A/cm 2 @12 K, 4T was found in the Nb3 (Al0·97 Cu0.03 ) wire, which is nearly four times of pure Nb3 Al sample. The Nb3 (Al0·97 Cu0.03 ) wire also shows the highest B irr value of 25.7T at 8 K and 12.9T at 12 K, respectively. The formed A15 phase exhibit uniform microstructure and composition. Flux pinning of the Nb3 (Al1- x Cu x ) wires follows the surface pinning mechanism, where grain boundary and stacking faults were considered as pinning centers. Highlights: Cu doping improved T c, layer J c and B irr of RHQT Nb3 Al superconducting wires. Cu addition lead to different A15 phase formation route in RHQT processed Nb3 Al. Layer J c of Nb3 Al1- x Cu x ( x = 0.03) wires reaches four times of pure Nb3 Al @12 K, 4T.